FLUKTUASI KEPADATAN MEGABENTOS DI PERAIRAN KENDARI, SULAWESI TENGGARA - Ucu Yanu Arbi; Paiga Hanurin Sawonua; Hendrik Alexander William Cappenberg (BERITA BIOLOGI, 2020)
Coral reef is an ecosystem which provides suitable habitats for sgroups of biota that has important ecological and economic values which can be used as bio-indicators to assess the health of the environment. Research on megabenthic fauna in Kendari waters and its surroundings, Southeast Sulawesi was carried out at nine permanent stations in 2015 to 2018. The data was collected using the Benthos Belt Transect method that modified from the Belt Transect method on 8 types or groups of megabenthos in these waters. The purpose of this study was to determine the density fluctuation of megabenthic fauna over the years. The mean density of individuals found at each station during the study did not differ significantly. The Kruskal-Wallis test on density of megabenthic fauna during this period of times did not show a significant difference (H = 28.511 > df 7 = 14.067). Drupella spp. was the group species of megabenthic fauna with the highest density each year (1,079-1,738 ind/ha), while lobster was the group species of megabenthic fauna with the lowest density each year (0 - 39.7 ind/ha). The crown of thorns starfish Acanthaster planci had the highest fluctuation where density increased from 28.3 to 71.4 ind/ha.